(untitled) (Indian Journal of Animal Production and Management, 2015)
A field study was conducted to identify constraints that hinder the dairy animal owners to adopt recommended scientific management practices in the Navsari district of South Gujarat. Majority of the respondents in the survey area were poor and major constraints observed related to housing, feeding and breeding management practices were lack of own capital, high cost of feeding and incidences of repeat breeding, respectively. These constraints are usually area specific and farmer specific. Hence, present study was planned to identify constraints that hinders them to adopt recommended scientific management practices in housing, feeding and breeding management of dairy animals in the Navsari district of south Gujarat.